Surgical and Injection Interventions for Dupuytren's Disease: A Systematic Review Protocol - Sabongi, Rodrigo Guerra; Moraes, Vinicius Ynoe de; Santos, João Baptista Gomes dos; Civile, Vinicius Tassoni; Carvas Junior, Nelson; Faloppa, Flávio (Revista Brasileira de Ortopedia, 2025)
To compare the effectiveness and safety of surgical and injection-based interventions for Dupuytren's disease (DD) using systematic review and network meta-analysis methodology.The current protocol follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) guidelines and is registered in The International Prospective Register of Systematic Reviews (PROSPERO). Randomized controlled trials involving adult patients with DD treated by surgical (e.g., fasciectomy, fasciotomy) or injection-based interventions (e.g., collagenase, corticosteroids) must be included. A comprehensive search must be conducted across MEDLINE, CENTRAL, EMBASE, LILACS, IBECS, and trial registries, without language or date restrictions. Two reviewers must perform independent screening, data extraction, and risk of bias assessment (RoB2). Primary outcomes must include functional improvement and adverse effects. Secondary outcomes must include recurrence, range of motion, and pain. Data synthesis should involve random-effects pairwise and network meta-analyses, with GRADE used to assess certainty of evidence. Subgroup analyses should explore heterogeneity based on clinical and methodological variables.This proposal of review aims to generate comparative estimates of effectiveness and safety across all eligible interventions, incorporating both direct and indirect evidence. Functional outcomes must be synthesized using a predefined hierarchy of patient-reported outcome measures (PROMs), and treatments must be ranked based on efficacy and safety profiles.The present systematic review aims to fill current evidence gaps by comparing all relevant interventions for DD, supporting clinical decision-making through robust synthesis of functional and safety outcomes.
Keywords: collagenases; Dupuytren contracture; fasciotomy; systematic review'